An Introduction to Methods of Backup and Disaster Recovery for Cloud Computing - Dubey, P; Choudhary, S (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing gives different sorts of administrations to its clients. storage as-a-service is one of the administrations gave by cloud framework in which extensive measure of electronic information is put away in cloud. As profitable and critical information of undertakings are put away at a remote area on cloud we should be guaranteed that our information is protected and be accessible whenever. In circumstances like flood, fire, quakes or any equipment breakdown or any coincidental erasure our information may never again stay accessible. To keep up the information well being there must be a few data backup procedure for cloud stage to recoup profitable and critical information productively in such circumstances said above. This paper gives a audit on different backup systems utilized for cloud computing stage in regards to this worr